Intercultural Competence in Healthcare: Challenges and Strategies for the Inclusion of Immigrant Population in Spain - Pena Díaz, Carmen; Sánchez Ramos, María del Mar (Círculo de Lingüística Aplicada a la Comunicación, 2026)
This article analyzes the growing cultural diversity in Spain as a result of immigration, with a specific focus on the impact on the healthcare system. It explores the theoretical frameworks of interculturality, cultural competence, and cultural sensitivity, and evaluates their implementation through regional healthcare protocols. Through a comparative analysis of models such as those by Campinha-Bacote, Purnell, Leininger, and Kleinman, as well as empirical research from Bas-Sarmiento et al. (2015) and Valero-Garcés (2019), this study offers a comprehensive review of challenges, strategies, and good practices in intercultural healthcare. It also proposes inclusive policies and culturally competent training to improve healthcare delivery to migrant populations in Spain.